2003
DOI: 10.1159/000072308
|View full text |Cite
|
Sign up to set email alerts
|

Differential Branching of the Sphingolipid Metabolic Pathways with the Stage of Development

Abstract: We have studied sphingomyelin metabolism in the papillae of neonatal (10-day-old) and adult (70-day-old) kidneys of male Wistar rats because sphingolipid second messengers generated by sphingomyelin metabolism are involved in cellular processes such as proliferation, differentiation and apoptosis. We showed that sphingomyelin and ceramide concentrations in homogenized rat papilla tissue increase with the time whereas sphingosine-1-phosphate content decreases. This is consistent with the finding of a higher bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Studies of sphingolipid content in kidneys of neonatal and adult rats found highest concentrations of S1P during the neonatal period that decreased with age, while ceramide and sphingomyelin content increased with age (11). Although these studies examined S1P content postnatally, the results are consistent with our findings of increased SPP activity and lower S1P content in mature kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…Studies of sphingolipid content in kidneys of neonatal and adult rats found highest concentrations of S1P during the neonatal period that decreased with age, while ceramide and sphingomyelin content increased with age (11). Although these studies examined S1P content postnatally, the results are consistent with our findings of increased SPP activity and lower S1P content in mature kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…In vitro studies show that such stimuli include hypoxia/reoxygenation [ 31 , 32 , 50 , 51 , 52 ], oxidants [ 33 , 53 , 54 ], UV light [ 38 , 39 , 55 ], heat stress [ 56 ], oxalate [ 54 , 57 ], P-fimbriae of E. coli [ 58 , 59 ], nephrotoxins, including cadmium [ 60 , 61 ], isoflurane [ 62 ], microcystin [ 63 ], nickel [ 64 ], and radiocontrast [ 65 ], Shiga-toxin B [ 58 ], staphylococcal enterotoxin B [ 66 ], interleukin (IL)-1β [ 59 ] and TNF-α [ 54 , 59 ]. In vivo studies show that ceramide is accumulated in kidneys exposed to anti-glomerular membrane (GBM) antibody [ 52 ], nephrotoxins such as carbon tetrachloride [ 67 ] and isoflurane [ 62 ], developing kidney [ 68 , 69 ], ischemia/reperfusion (I/R) injury [ 51 , 52 ], glycerol-induced myohemoglobinuria [ 52 ], and obstructive nephropathy [ 70 ]. These stimuli can induce apoptosis, and an apoptogenic role of ceramide is further supported by the ability of exogenous ceramide to induce apoptosis in RTCs [ 50 , 63 , 68 , 71 ].…”
Section: Ceramide-induced Apoptosismentioning
confidence: 99%
“…We have previously reported that renal collecting duct cells regulate the branching of sphingolipid metabolism depending on the stage of cellular differentiation (25). Further, we demonstrated that, during hypertonicity-induced differentiation, MDCK cells develop a program of sphingolipid metabolism that includes a FB1-resistant increase in GSLs (14) and SM synthesis (15).…”
Section: Discussionmentioning
confidence: 75%